2010
DOI: 10.1371/journal.pntd.0000795
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microscopy and Alamar Blue Reduction in a Larval Based Assay for Schistosome Drug Screening

Abstract: BackgroundIn view of the current widespread use of and reliance on a single schistosomicide, praziquantel, there is a pressing need to discover and develop alternative drugs for schistosomiasis. One approach to this is to develop High Throughput in vitro whole organism screens (HTS) to identify hits amongst large compound libraries.Methodology/Principal FindingsWe have been carrying out low throughput (24-well plate) in vitro testing based on microscopic evaluation of killing of ex-vivo adult S. mansoni worms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
96
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 21 publications
6
96
0
Order By: Relevance
“…Motility, together with other microscopic characteristics (e.g. shape alterations and granularity) (Butterworth et al 1982) currently comprise the most common indicators for assessing schistosome viability and represent the 'gold standard' for assessing drug screening protocols and determining RNAi phenotype within the schistosomiasis research community (Abdulla et al 2009, Mansour and Bickle 2010, Štefani et al 2010). However, despite its wide application, bright-field, light microscopic assessment of schistosome viability has several inherent problems.…”
Section: Whole Organism Approaches Used To Quantify Schistosoma Viabimentioning
confidence: 99%
See 1 more Smart Citation
“…Motility, together with other microscopic characteristics (e.g. shape alterations and granularity) (Butterworth et al 1982) currently comprise the most common indicators for assessing schistosome viability and represent the 'gold standard' for assessing drug screening protocols and determining RNAi phenotype within the schistosomiasis research community (Abdulla et al 2009, Mansour and Bickle 2010, Štefani et al 2010). However, despite its wide application, bright-field, light microscopic assessment of schistosome viability has several inherent problems.…”
Section: Whole Organism Approaches Used To Quantify Schistosoma Viabimentioning
confidence: 99%
“…The development of high content screening systems, as previously discussed, is an important step on the road to developing real time visualisation data for all schistosome lifecycle stages. However, while there have been calls for its development (Mansour and Bickle 2010), there is no published evidence that this has been achieved to date.…”
Section: Whole Organism Approaches Used To Quantify Schistosoma Viabimentioning
confidence: 99%
“…Even though several new drug discovery techniques have been developed in the recent past, methodologies in pharmaceutical drug discovery for schistosomiasis lack elaboration, interlaboratory standardization, harmonization, and automation (9)(10)(11)(12)(13). This is in contrast to other povertyrelated diseases, such as malaria, where tremendous attention and support in the last 10 years by The Global Fund, a nongovernmental funding organization, have allowed the development of elaborate drug discovery programs (14).…”
mentioning
confidence: 99%
“…Even though the handling of schistosomula allows automation, at least to a certain degree, the viability of the worms, which determines the drug's activity, is commonly assessed by microscopy. To overcome the subjectivity and complexity of microscopy, several novel techniques to determine schistosomulum viability have recently been presented, although microscopy is still the standard reference methodology (12,13,15,16). However, the phenotype and the degree of changes in the worms' morphology and motility heavily depend on the chemical nature of the drug, and in adult worms it has been shown that damaged tissues have the potential to regenerate (17,18).…”
mentioning
confidence: 99%
“…Several studies have therefore been launched in the recent past. These have explored novel tools to facilitate the readout of in vitro drug screening on schistosomes, such as fluorescence-labeled albumin (14), fluorophores (propidium iodide and fluorescein diacetate) (29), and colorimetric assays with alamarBlue (25).…”
mentioning
confidence: 99%